Artificial lamina after laminectomy: Progress, applications, and future perspectives - Yue, Jing; Han, Qing; Chen, Hao; Zhang, Aobo; Liu, Yang; Gong, Xuqiang; Wang, Yang; Wang, Jincheng; Wu, Minfei (Frontiers in Surgery, 2023)
In clinical practice, laminectomy is a commonly used procedure for spinal decompression in patients suffering from spinal disorders such as ossification of ligamentum flavum, lumbar stenosis, severe spinal fracture, and intraspinal tumors. However, the loss of posterior column bony support, the extensive proliferation of fibroblasts and scar formation after laminectomy, and other complications (such as postoperative epidural fibrosis and iatrogenic instability) may cause new symptoms requiring revision surgery. Implantation of an artificial lamina prosthesis is one of the most important methods to avoid post-laminectomy complications. Artificial lamina is a type of synthetic lamina tissue made of various materials and shapes designed to replace the resected autologous lamina. Artificial laminae can provide a barrier between the dural sac and posterior soft tissues to prevent postoperative epidural fibrosis and paravertebral muscle compression and provide mechanical support to maintain spinal alignment. In this paper, we briefly review the complications of laminectomy and the necessity of artificial lamina, then we review various artificial laminae from clinical practice and laboratory research perspectives. Based on a combination of additive manufacturing technology and finite element analysis for spine surgery, we propose a new designing perspective of artificial lamina for potential use in clinical practice.